Enhancing User Experience in Forex Mobile Trading Application to Support Customer Relationship Management - Hans Andre Martinus Supit; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACT                        This study will examine the usefulness and convenience of MIFX Mobile trading applications for customers and as part of CRM applications that can help the company grow in the long term and have a competitive advantage against traditional trading platform.            This research uses qualitative descriptive and purposive sampling technique by interviewing four informants who uses the application in their daily life. The data analysis techniques that were used are analysis of Miles, Huberman and Saldana by conducting data condensation, data presentation and drawing conclusions or verification. The results of the interviews and the data that have been obtained is processed and verified by using triangulation system of data sources.             The results of this study indicate that convenience is the main reason that makes customers use the application, then followed by usability and security as well as referral features, which makes it easier to make an introduction to prospective new customers (Word of Mouth). These innovative features in addition to making it easier for customers to make transactions, also provide feedback to the company.            The needs of accurate information system and faster news should be adjusted with the growth of the information technology. Innovative Customer Relationship Management (CRM) strategy is increasingly needed by companies to grow. Applications are one of the ways that companies can use as part of CRM where there is an ongoing interaction between customers and companies so that they are interrelated in creating a customer experience (User Experience).            In the future, this research study is expected to assist customers in making a better transaction and useful for companies in taking holistic CRM application approach which includes customer experience and customer collaboration for the future growth of the company and developing strategy for future growth.